The cottage in the woods - Coville, Katherine (Alfred A. Knopf, 2015)
Presents the story of "Goldilocks and the Three Bears" as told by young Teddy's governess, who came to work at the Vaughn family "cottage" shortly before a golden-haired girl, ragged and dirty, entered the home and soon became a beloved foster child, until evil characters tried to take her away.